Broadband Internet Access and the Digital Divide : Federal Assistance Programs. (U.S. Congressional Research., 2008)
Examines the issue of broadband Internet access and the "digital divide," a term used to describe the lack of access to and use of telecommunications technologies among low-income and other underserved communities. Considers the Federal role in telecommunications development, including FCC and Rural Utilities Service programs. Summarizes legislation in the 109th and 110th Congresses regarding broadband deployment assistance, and examines related policy issues.